Advanced treatment of coal chemical reverse osmosis concentrate with three-stage MABR. Issue 17 (10th March 2020) - Liu, Rukang; Wang, Qin; Li, Mei; Liu, Jun; Zhang, Wei; Lan, Meichao; Du, Chunyu; Sun, Zhiye; Zhao, Dong; Li, Baoan
Abstract : A MABR system was constructed to treat coal chemical reverse osmosis concentrate without an external carbon source. Abstract : The issue of reverse osmosis concentrate (ROC) has attracted significant attention due to its complex and toxic constituents under high salinity conditions. In this work, a three-stage membrane-aerated biofilm reactor (MABR) system was constructed to treat such wastewater without an external carbon source. The effects of operating conditions including aeration pressure, reflux ratio, temperature and hydraulic retention time on the removal performance of the integrated system were evaluated and optimized. Under the optimal operating parameters, the removal efficiencies of COD, NH4 + –N, NO3 − –N, and TN reached 69.36%, 80.95%, 54.55%, and 54.36%, respectively. Three-dimensional fluorescence analysis indicated that humic acid was mostly removed from raw water. Moreover, microbial diversity analysis indicated that the microbial community structure of each reactor could be individually modulated to exert different functions and enhance the system performance. The integrated MABR system exhibits great feasibility and potential for the advanced treatment of coal chemical ROC.